Recursos didácticos para la enseñanza de matemática del tercer grado en la Escuela General Manuel Serrano Renda, El Guabo, 2021-2022. - Gorozabel Olivo, Nora Maria; Sánchez Chalen, Viviana Mercedes (Machala, Universidad Técnica de Machala, 2022)
The study work is directed towards the investigation of didactic means to teach mathematics in the third year at the "Manuel Serrano Renda" general school. In the development of this project, the educational context where the object of study was located was known, in this way it was possible to obtain a clear vision of the problems established in this investigation. To collect the necessary information, instruments such as the observation guide, survey, interview were used; whose result was the inadequate handling of pedagogical materials by the educators for numerical teaching, consequently, it made it easier for the researchers to find a solution to this problem. This study was based on the deductive and inductive mode, where various hypotheses were raised allowing to corroborate if these were false or true; On the other hand, the quantitative-qualitative approach was used to obtain assertive results from the survey applied to the students and characteristic data of the established conflict. This research has a level that was projected from the descriptive, explanatory and relational, in combination with the field and bibliographical investigative modality. By obtaining the results, the value of the intervention of educational material was concluded that contribute significantly to the advancement of the exact rational judgment in the students, and these in turn allow the creation of classroom environments aimed at the motivation and participation of the same during the academic hours in the teachinglearning processes, leaving behind the traditional pedagogy to give way to a constructivist education. Based on the above, the realization of a didactic guide that contains various types of didactic resources that facilitate linking theory with practice regarding basic operations applied to third grade is proposed, each didactic instrument consists of objectives, skills, methodology either by study anchored in unknowns or in turn by an open standard sustained in numbers, procedure and assessment according to the topic to be addressed; This document is made up of traditional, manipulative, illustrative teaching tools and those supported by technology. This material will be available to teachers when they need it or its use is convenient. Consequently, this didactic instrument is projected to strengthen the application of didactic resources in teaching competencies aimed at the numerical area; In this context, this instruction, apart from being a support material in the teaching exercise, aims to achieve the goals established in the educational curriculum for the benefit of the integral development of the individual, so that he or she is able to solve problems of daily life. An excellent didactic resource must have the ability to establish teaching-learning scenarios for students, it must favor the different attitudes of students towards numbers,it must be adaptable to the needs of each student so that they are the protagonists of theirown knowledge. ; In other words, this intervention seeks to objectively satisfy thecurricular contents with respect to the benefit of the educational community, in such a way as to provide a quality and warm education that society needs so much
El trabajo de estudio se encamina en la indagación de medios didácticos para enseñar matemática en tercer año en la escuela general “Manuel Serrano Renda”. En el desarrollo de este proyecto se conoció el contexto educativo donde se ubicó el objeto de estudio, de esta manera se pudo obtener una visión nítida sobre la problemática establecida en esta investigación. Para recopilar la información necesaria se usó instrumentos como la guía de observación,encuesta, entrevista; cuyo resultado fue el manejo inadecuado de materiales pedagógicos por parte de las educadoras para la enseñanza numérica, en consecuencia, facilito a las investigadoras buscar una solución a este problema.Este estudio tuvo como base el modo deductivo e inductivo, en donde suscitaron diversas hipótesis permitiendo corroborar si estas fueron falsas o verdaderas; por otro lado, se manejó el enfoque cuanti-cualitativo para obtener resultados asertivos del sondeo aplicado a los alumnos y datos característicos del conflicto establecido. Esta investigación tiene un nivel que se proyectó desde lo descriptivo, explicativo y relacional, en combinación con la modalidad investigativa de campo y bibliográfica Mediante la obtención de los resultados se concluyó el valor de la intervención de material educacional que contribuyan significativamente al avance del juicio racional exacto en las y los discentes, y estos a su vez permitan crear ambientes áulicos direccionados a la motivación y participación de los mismos durante las horas académicas en los procesos de enseñanza – aprendizaje, dejando atrás la pedagogía tradicional para dar paso a una educación constructivista. En función a lo expuesto anteriormente, se plantea la realización de una guía didáctica que contiene diversos tipos de recursos didácticos que faciliten vincular la teoría con la práctica referente a las operaciones básicas aplicadas a tercer grado, cada instrumento didáctico consta de objetivos, destrezas, metodología ya sea por estudio anclado en incógnitas o a su vez por norma abierta sostenida en números, procedimiento y valoración según el tema que se desee abordar; este documento se constituye por herramientas didácticas tradicionales, manipulativas, ilustrativas y las que están apoyadas en la tecnología, este material estará a la disposición de las maestras cuando lo necesiten o sea conveniente su utilización. Consecuentemente, este instrumento didáctico se proyecta a fortalecer la aplicación de recursos didácticos en las competencias docentes encaminadas al área numérica; en este contexto, este instructivo aparte de ser un material de apoyo en el ejercicio docente pretende alcanzar las metas establecidas en el currículo educativo en beneficio al desarrollo integral del individuo, para que este sea capaz de poder resolver problemáticas del diario vivir. Un excelente recurso didáctico debe tener la capacidad de establecer escenarios de enseñanza – aprendizaje para los estudiantes, debe favorecer las diferentes actitudes de los discentes ante los números, debe ser adaptable a las necesidades de cada estudiante para que estos sean los protagonistas de sus propios conocimientos; en otras palabras, mediante esta intervención se busca satisfacer objetivamente los contenidos curriculares respecto al beneficio de la colectividad educativa, de tal manera se brinde una educación de calidad y calidez que tanto la sociedad necesita
Keywords: RECURSO DIDACTICO; PENSAMIENTO LOGICO MATEMATICO; ENSEÑANZA; APRENDIZAJE